2012
DOI: 10.1371/journal.pone.0052297
|View full text |Cite
|
Sign up to set email alerts
|

First Insights into the Phylogenetic Diversity of Mycobacterium tuberculosis in Nepal

Abstract: BackgroundTuberculosis (TB) is a major public health problem in Nepal. Strain variation in Mycobacterium tuberculosis may influence the outcome of TB infection and disease. To date, the phylogenetic diversity of M. tuberculosis in Nepal is unknown.Methods and FindingsWe analyzed 261 M. tuberculosis isolates recovered from pulmonary TB patients recruited between August 2009 and August 2010 in Nepal. M. tuberculosis lineages were determined by single nucleotide polymorphisms (SNP) typing and spoligotyping. Drug … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 54 publications
4
26
2
Order By: Relevance
“…Both of the human isolates had spoligotype SIT138 categorized as EAI5, 22 which is the most frequently observed EAI type in this country. 25 This SNP seems to have occurred on a specific lineage of the clade, since other EAI5-SIT138 isolates obtained in Nepal did not have the SNP (Figure 3). …”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Both of the human isolates had spoligotype SIT138 categorized as EAI5, 22 which is the most frequently observed EAI type in this country. 25 This SNP seems to have occurred on a specific lineage of the clade, since other EAI5-SIT138 isolates obtained in Nepal did not have the SNP (Figure 3). …”
Section: Discussionmentioning
confidence: 91%
“…22,25 This lineage is predominantly observed in Indo-Oceanic areas like south India or the Philippines; 31,32 however, its prevalence in Nepal is relatively low. In the recent report, 25 the prevalence of Indo-Oceanic lineage was 11.5% in Nepal and our observation results were also very similar (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A key factor is the geographical location of Nepal, interlocked between China and India, two countries, which together account for approximately a third of annual global new cases (11% and 24%, respectively) [1]. A recent study of 261 Nepalese isolates found any drug resistance (any drug resistance has been defined as resistance to isoniazid, rifampicin, streptomycin, ethambutol, fluoroquinolones, and/or aminoglycosides) in 12.8%% of Mtb strains that were new untreated cases, with the most frequent lineages reported as CAS/Delhi (40.6%), East Asian (including Beijing) (32.2%), Euro-American (15.7%) and Indo-oceanic (11.5%) [13]. To gain further insight into the characteristics and diversity of Mtb in Nepal, our study aimed to categorise isolates for the first time using IS6110 FAFLP PCR and to assign them to different genetic lineages.…”
Section: Introductionmentioning
confidence: 99%
“…The elephant B isolate belonged to the Indo-Oceanic lineage (East African–Indian 5 spoligo-international type 1365) (Table). The prevalence of the Indo-Oceanic lineage among human TB patients in Nepal is only 11.5% ( 8 ). The drug resistance–associated region sequences rpoB , katG , inhA promoter region, and gyrA were all wild types in both isolates.…”
mentioning
confidence: 99%